A novel concept of bicarbonate-carbon utilization via an absorption-microalgae hybrid process assisted with nutrient recycling from soybean wastewater. (10th November 2019) - Song, Chunfeng; Qiu, Yiting; Li, Shuhong; Liu, Zhengzheng; Chen, Guanyi; Sun, Luchang; Wang, Kailiang; Kitamura, Yutaka
Abstract: A novel ammonia absorption-microalgae hybrid CO2 capture and conversion process was investigated in this study. Using rich ammonia solution (ammonium bicarbonate) as a nutrient source for microalgae cultivation, the challenge of energy-intensive regeneration may potentially be overcome. To provide other nutrients for microalgae apart from ammonium bicarbonate, soybean wastewater was used to replace BG-11 medium for resource recycling and could adjust the pH of cultivation solution to reduce the threat of NH3 escape and inhibition. Chlorella sp. L166 and L38 were cultivated in ammonium bicarbonate solution using 5-times and 10-times diluted soybean wastewater under two culture modes (direct and batch feeding). The experimental results indicated that microalgae growth could be promoted by using 5-times diluted soybean wastewater as a cultivation medium with a removal rate of 50–65% COD, 70–80% NH3 -N and 95–100% TP from a wastewater purification perspective. In the hybrid system, the NH3 escape ratio decreased to 15.8% with a carbon conversion efficiency of over 60%, and effectively achieved carbon and nitrogen utilization with 78.8 mg/L/d of microalgae biomass. Graphical abstract: Image 1 Highlights: CO2 conversion efficiency of hybrid process was enhanced by adding soybean wastewater. pH of microalgae cultivation was adjusted via different diluted soybean wastewater. NH3 escape reduced via adding soybean wastewater in absorption-microalgae hybrid process. 78.8 mg/L/d biomass could be obtained via the advanced absorption-microalgae hybrid process.